Mucin-producing tumor of the pancreas: a case report - Hasan ÖZKAN,; Hiromitsu SAISHO,; Taketo YAMAGUCHI,; Takeshi ISHIHARA,; Toshio TSUYUGUCHI,; Yasuharu KIKUCHI,; Masao OHTO, (Turkish Journal of Gastroenterology, 2020)
-